Schatten class operators on the Bergman space over bounded symmetric domain
Let Ω be a bounded symmetric domain in C^n with Bergman kernel K(z, w). Let dV_λ(z)=K(z, z)dV(z)C_λ , where C_λ=_ΩK(z, z)^λdV(z), λR, dV(z) is the volume measure of Ω normalized so that K(z, 0)=K(0, w)=1. In this paper we have shown that if the Toeplitz operator T_φ defined on L_a^2(Ω, dVC_0 ) belongs to the Schatten p-class, 1≤ p, number=3, journal=Methods of Functional Analysis and Topology, author=Sahoo, M. and Das, N., year=2014, month=Sep., pages=193–212